2021
DOI: 10.2196/26540
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Depression From Smartphone Behavioral Markers Using Machine Learning Methods, Hyperparameter Optimization, and Feature Importance Analysis: Exploratory Study

Abstract: Background Depression is a prevalent mental health challenge. Current depression assessment methods using self-reported and clinician-administered questionnaires have limitations. Instrumenting smartphones to passively and continuously collect moment-by-moment data sets to quantify human behaviors has the potential to augment current depression assessment methods for early diagnosis, scalable, and longitudinal monitoring of depression. Objective The obj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 87 publications
1
66
0
Order By: Relevance
“…This is not surprising; clinical studies intentionally measure symptoms of a specific serious mental illness (SMI), while non-clinical studies collect measures on more prevalent symptoms across the general population (e.g. depression, stress) [ 3 , 5 , 17 , 20 ]. That being said, symptoms of depression are symptoms of SMIs, including schizophrenia [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising; clinical studies intentionally measure symptoms of a specific serious mental illness (SMI), while non-clinical studies collect measures on more prevalent symptoms across the general population (e.g. depression, stress) [ 3 , 5 , 17 , 20 ]. That being said, symptoms of depression are symptoms of SMIs, including schizophrenia [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equipping smartphones and wearables to capture moment-by-moment datasets with sensing apps has made it possible to collect datasets passively and in naturalistic settings. Inherent in these datasets are behavioral patterns: routines, rhythms, activities, and interactions that are useful indicators of depression [ 61 ].…”
Section: Data Miningmentioning
confidence: 99%
“…In another study, Saeb et al [ 32 ] found significant correlations between depression and passive data such as phone use and GPS in a sample of 40 participants. Asare et al [ 33 ] found that age group and gender as predictors led to improved machine learning performance. Their study concluded that behavioral markers indicative of depression can be unobtrusively identified using smartphone sensor data [ 33 ].…”
Section: Introductionmentioning
confidence: 99%